Inactivation modeling of microorganisms using organic chlorine and acetic acid solutions and estimation of growth kinetics of adhered Enterobacteriaceae to lettuce (Lactuca sativa L.) - Alves, Roberta B. T.; Mousavi Khaneghah, Amin; Antunes, Maria A.; Silva, Beatriz S.; Sant'Ana, Anderson S.; Peña, Wilmer E. L.; Andrade, Nélio J. (Journal of food safety, 2020)
This study was aimed to evaluate the efficiency of the organic chlorine and acetic acid solutions on the inactivation of adhered cells of Escherichia coli, Cronobacter sakazakii and Klebsiella pneumoniae to lettuce. Besides, the growth and inactivation of K. pneumoniae adhered to lettuce was modeled. According to the findings, the use of chlorine solution (170 mg/ml of total residual chlorine) caused reductions of 1.8, 1.9, and 1.9 log for E. coli, C. sakazakii, and K pneumoniae, respectively, were recorded. In this regard, the organic chloramine was more effective in controlling the adhered microorganisms while compared with 1.5% acetic acid solution, while the addition of 0.5% sodium chloride to 1.5% acetic acid solution increased microbial inactivation. K. pneumoniae RC‐34 inactivation was characterized by the presence of two sub‐populations with different resistances against the proposed sanitizers. Moreover, the growth kinetic parameters of K. pneumoniae RC‐34 adhered to lettuce leaves were very similar to that reported in the literature for nonadhered microorganisms. The predictive data generated can be valuable to assess the growth and inactivation of produce adhered microorganisms in leafy produce.